ControlH: an algorithm specification language and code generator - Englehart, M.; Jackson, M. (IEEE control systems, 1995)
In this article, we describe the language and code generator ControlH. The development of ControlH is being supported by the ARPA domain-specific software architectures (DSSA) program. The language is designed for describing guidance, navigation, and control (GN&C) algorithms in a concise yet rigorous manner. Both textual and graphical syntaxes exist. The code generator generates high-quality, modular Ada or C from ControlH specifications. Together, the language and the code generator provide software reuse and configuration at the level of the GN&C algorithm specification.< >